Can supplementation of vitamin D improve aerobic capacity in well trained youth soccer players? - Jastrzebska, M.; Kaczmarczyk, M.; Michalczyk, M.; Radziminski, L.; Stepien, P.; Jastrzebska, J.; Wakuluk, D.; Diaz Suárez, A.; López Sánchez, G. F.; Cieszczyk, P.; Godlewski, P.; Krol, P.; et al. (Journal of Human Kinetics, 2018)
There is no clear evidence that vitamin D effectively improves physical capacity in high-level athletes. The aim of this study was to confirm that vitamin D supplementation of soccer players during eight-week high-intensity training would have a significant effect on their aerobic capacity. The subjects were divided into two groups: the experimental one that was supplemented with vitamin D (SG, n = 20), and the placebo group (PG, n = 16), not supplemented with vitamin D. All the players were subjected to the same soccer training described as High-Intensity Interval Training (HIIT). The data of the vitamin D level, PWC170, lactate threshold (LT) were collected just before and after the intervention. A significant increase in vitamin D concentration (119%) was observed in the supplemented group, while the non-supplemented group showed a decrease of 8.4%. The studied subjects improved VO2max results by 20% in the SG, and by 13% in the PG. The improvement in velocity at the LT was similar in both groups. Results of this study show that vitamin D can have a positive, though moderate, effect on aerobic performance in players subjected to high-intensity training in the form of small-sided games for 8 weeks.